EFFECT OF INCUBATION PERIOD ON PLATE COUNT OF RAW ICED AND FROZEN FISH - THAMPURAN, NIRMALA; IYER, H KRISHNA; IYER, K MAHADEVA (Fishery Technology, 2017)
The total viable counts were estimated in one hundred and sixty five samples of raw, iced and frozen fish using incubation periods of 24, 48, 72 and 96 h. For raw fish, 24 h and for iced and frozen :fish 48 h incubation of the plates were found to be adequate. Variation between samples was significant at 1% level for raw iced and frozen samples.